MR neurography for the evaluation of CIDP. Issue 4 (26th December 2016) - Ishikawa, Tomomasa; Asakura, Kunihiko; Mizutani, Yasuaki; Ueda, Akihiro; Murate, Ken‐Ichiro; Hikichi, Chika; Shima, Sayuri; Kizawa, Madoka; Komori, Masako; Murayama, Kazuhiro; Toyama, Hiroshi; Ito, Shinji; et al.
ABSTRACT: Introduction : To visualize peripheral nerves in patients with chronic inflammatory demyelinating polyneuropathy (CIDP), we used MR imaging. We also quantified the volumes of the brachial and lumbar plexus and their nerve roots. Methods : Thirteen patients with CIDP and 12 healthy volunteers were enrolled. Whole‐body MR neurography based on diffusion‐weighted whole‐body imaging with background body signal suppression (DWIBS) was performed. Peripheral nerve volumes were calculated from serial axial MR images. Results : The peripheral nervous system was visualized with 3‐dimensional reconstruction. Volumes ranged from 8.7 to 49.5 cm 3 /m 2 in the brachial plexus and nerve roots and from 10.2 to 53.5 cm 3 /m 2 in the lumbar plexus and nerve roots. Patients with CIDP had significantly larger volumes than controls ( P < 0.05), and volume was positively correlated with disease duration. Conclusions : MR neurography and the measurement of peripheral nerve volume are useful for diagnosing and assessing CIDP. Muscle Nerve 55 : 483–489, 2017